Fundamentals of Entrepreneurship (ENT300) : Lavadora Laundry / Afifuddinfitri Zainuddin … [et al.] - Zainuddin, Afifuddinfitri; Mohamad Mahin, Mohamad Khalid; Abdul Manan, Mohamad Azri; Awang Jos, Dayang Nur Syaza; Shamsulbahri, Nur Amanina (2018)
Lavadora is the name that has been chosen by the suggestion from one ofthe partners in this company. This name has been chosen based on the Spanish language which islaundry being translate to become Lavadora. Our business is a home laundry services.Our business also provide delivery services which you can call +6011 255 3333.